PENINGKATAN PRODUKTIVITAS PETANI TANAMAN KOPI PEMANFAATAN TEKNOLOGI MESIN PENGERING KOPI BAHAN BAKAR BRIKET SEBAGAI BAHAN BAKAR ALTERNATIF - Duwi Leksono Edy; Widiyanti; Erwin Komara Mindarta (Bahasa Indonesia, 2019)
The purpose of this is to increase the productivity of coffee crop husbandman by utilizing appropriate technology that functions for drying coffee. The coffee dryer uses fuel in the form of charcoal which is produced from coffee skin waste which becomes environmental waste. With the application of appropriate technology, the community of coffee farmers can make the process of drying coffee quickly without requiring considerable time. Community service activities are carried out in Tirtoyudo Village, Tirtoyudo District, Malang Regency by applying a coffee dryer oven machine using briquette fuel. The results of community service activities are: (a) the fulfillment of environmentally friendly and inexpensive energy sources for the process of drying coffee for partners in particular and the people of Tirtoyudo Village in general through the use of coffee waste as briquette fuel; (b) the fulfillment of coffee dryer with briquette fuel energy for partners in Tirtoyudo Village so that the process of drying coffee beans is more effective and efficient; (c) availability of standardized packaging production equipment for ground coffee for partners in Tirtoyudo Village so that the quality and price of partner coffee powder can compete in the market; (d) online marketing so that production can reach exports for sales, and (d) the socio-economic activities of the Tirtoyudo Village community become more qualified through small business groups drying coffee beans and processing coffee grounds.